Obesity in childhood - literature review and educational recommendations - Kiełczewska, Aleksandra; Szcześniak, Grzegorz; Kiełczewska, Anna (Journal of Education, Health and Sport, 2024)
Introduction and purpose Childhood obesity is a major global health concern. The World Health Organization reports that the prevalence of obesity in children and adolescents has increased significantly from 4% in 1975 to over 18% in 2016. The aim of the study is to conduct a comprehensive review of the literature on obesity among children and adolescents, emphasizes the importance of prevention, identification and effective management of childhood obesity. Materials and methods An extensive examination of articles published in scientific journals was carried out through online research platforms PubMed and Google Scholar. We searched articles by entering keywords in appropriate configuration: “childhood obesity”, “pediatric overweight”, “physical activity”, “activity and health”, “diet and obesity", "bariatric surgery" and "obesity medication". State of knowledge Treating childhood obesity requires following a personalized weight loss program, as well as adopting healthy eating habits and lifestyle practices. Improvements in metabolic and anthropometric indices can be achieved through complex interventions including dietary modification and physical activity, behavioral therapy, health promotion education, pharmacological treatment and bariatric surgery A step-by-step approach to managing weight is recommended, considering the child's age, the severity of obesity, and any accompanying health conditions. Dietary interventions focus on promoting a balanced, nutrient-rich diet that is calorie-appropriate for the child's age and gender. Summary Further research is still necessary to develop additional pharmaceutical options, refine surgical techniques, and better understand long-term outcomes in this patient population.To effectively prevent this disease, a comprehensive approach is necessary, considering both education and changes in the social environment.